2016
DOI: 10.14419/ijbr.v4i2.6434
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of kojic acid producing isolate of Aspergillus oryzae potentially applicable for production from sugarcane molasses

Abstract: Kojic acid is an organic acid produced as secondary metabolite by different fungi specially Aspergillus species. Isolation of a novel fungal strain potential for kojic acid production from agro-industrial wastes was the main purpose of the present study. Kojic acid was estimated in the current investigation colorimetric by 2,6-dichlorophenolindophenol (DCIP). A total of 43 fungal isolates belonging to seven species of Aspergillus recovered from stored wheat grains and dust air were screened for their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…has the ability to produce invertase enzyme for the hydrolysis of sucrose to glucose and fructose for subsequent transformation into KA. Rasmey et al (2016) reported that glucose and sucrose followed by starch are most suitable sources for KA production, while no detected acid was produced in the presence of maltose and cellulose as carbon sources.…”
Section: Optimization Of Kojic Acid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…has the ability to produce invertase enzyme for the hydrolysis of sucrose to glucose and fructose for subsequent transformation into KA. Rasmey et al (2016) reported that glucose and sucrose followed by starch are most suitable sources for KA production, while no detected acid was produced in the presence of maltose and cellulose as carbon sources.…”
Section: Optimization Of Kojic Acid Productionmentioning
confidence: 99%
“…The releasing sugars significantly affect the KA production by the experimental mutant strains. The previous studies recorded that the amounts of KA excreted in the culture medium depend significantly on the type of fermentable sugars consumed by fungal strains (Rasmey et al 2016). The differences between both mutant strains in their productivity of KA from raw materials, either with increase or decrease about WT strain, may result in difference in their ability to recover the mutated genes.…”
Section: Improvement Of Kojic Acid Production By Mutagenesismentioning
confidence: 99%
“…Kojic acid (5-hydroxy-2-hydroxymethyl-γpyrone) is a natural organic acid was initially extracted from fermented steamed rice (known as "koji" in Japanese) in Japan by Saito in 1907 1 . Kojic acid is a secondary metabolite formed during aerobic fermentation of carbohydrates by several species of fungi as well as some bacterial strains of the two bacterial genera Acetobacter and Brevibacterium [2][3][4] . Aspergillus and Penicillium species are widely known among fungi as the best kojic acid producers 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the food processing, it is used as a precursor of flavors and as a preserving material in agricultural products during storage, especially vegetables and fruits by inhibiting the polyphenol oxidase (PPO) action 13 . Kojic acid is documented in different studies as a precursor or an intermediate compound in chemicals production that can be used as therapeutic agents 3 . At the carbon 5 of pyrone ring, the hydroxyl group acts as a weak acid, make it is able to form salts with some metals like sodium, zinc, calcium, and cadmium 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanical, physical, chemical and biological processes can be used for agro-industrial wastes pretreatment [11][12][13]. Mechanical pretreatment is grinding step that usually performed to reduce the particle size crystallinity before subsequent processing steps.…”
Section: Introductionmentioning
confidence: 99%